Critical neuroscience—or critical science? A perspective on the perceived normative significance of neuroscience - Schleim, Stephan (Frontiers in Human Neuroscience, 2014)
Members of the Critical Neuroscience initiative raised the question whether the perceived normative significance of neuroscience is justified by the discipline’s actual possibilities. In this paper I show how brain research was assigned the ultimate political, social, and moral authority by some leading researchers who suggested that neuroscientists should change their research priorities, promising solutions to social challenges in order to increase research funds. Discussing the two examples of cognitive enhancement and the neuroscience of (im)moral behavior I argue that there is indeed a gap between promises and expectations on the one hand and knowledge and applications on the other. However it would be premature to generalize this to the neurosciences at large, whose knowledge-producing, innovative, and economic potentials have just recently been confirmed by political and scientific decision-makers with the financial support for the Human Brain Project and the BRAIN Initiative. Finally, I discuss two explanations for the analyzed communication patterns and argue why Critical Neuroscience is necessary, but not sufficient. A more general Critical Science movement is required to improve the scientific incentive system.